PENGEMBANGAN INSTRUMEN LITERASI MATEMATIS BERBASIS ETNOMATEMATIKA UNTUK PESERTA DIDIK SEKOLAH DASAR - Fauzi, Asri; Rahmatih, Aisa Nikmah; Ermiana, Ida; Nurmawanti, Iva (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
This study aims to develop an ethnomathematics-based mathematical literacy instrument for elementary school students, which will be reviewed in terms of validity, reliability, level of difficulty, and discrimination power. The type of research used is Research and Development (R&D) with the Tessmer Formative Evaluation development model consisting of preliminary stages, self-evaluation, and prototyping stages (consisting of expert review, one-to-one, small group, and field test). The subjects of this study were 30 elementary school students. The data analysis techniques used were validity, reliability, difficulty level and discrimination power tests. The results of this study indicate that the ethnomathematics-based mathematical literacy instrument is valid based on the results of the expert review test. The reliability of the mathematical literacy instrument obtained a Cronbach's alpha value of 0.687. The mathematical literacy instrument's difficulty level was 40% for questions in the easy category and 60% for questions with a moderate level of difficulty. Meanwhile, from the results of the instrument difference test, 33% were in the weak category, 27% in the mild category, 33% in the good category, and 7% in the better category. The results of the development of mathematical literacy instruments based on ethnomathematics concluded that the test instrument met the eligibility criteria, namely meeting the elements of validity, reliability, level of difficulty and good discrimination so that it is suitable for use.